PENGARCAAN DEWA WISNU PADA MASA HINDU-BUDDHA DI BALI (ABAD VII-XIV MASEHI) - I Kadek Sudana Wira Darma (Forum Arkeologi, 2019)
Figurine of goddess Vishnu is an archaeological remain of Hindu-Buddhist period that rarely found in Bali. This research examines the variation of iconography, as well as the role and the position of Vishnu in the Hindu-Buddhist period in Bali in VII-XIV Century AD. The purpose of this research is to reconstruct the history of Balinese culture in the past, especially in the religion aspect. The methods of data collection are literature study, observation and interviews as well as data processing through the analysis of comparative iconography, and iconoplastic. The theory that used to assist analysis is a theory of religious iconology and iconography of Erwin Panofsky. Based on the results of the study found that there is a variation of the iconography on the statues of Vishnu in Hindu-Buddhist period in Bali. The variation can be seen in the variety of depictions of jewelry, clothing, “laksana” and posture. There are also variations for the iconography that caused by the factors of the ability and creativity of the artists, social restriction, cultural influence and raw material of the statue. The role and position of Vishnu in the Hindu-Buddhist period in Bali as a protector and preserver. His position is important although it is not as high as the god of Shiva. Arca Dewa Wisnu merupakan tinggalan arkeologi dari periode Hindu- Buddha yang sangat sedikit ditemukan di Bali. Penelitian ini meneliti variasi ikonografi, serta peranan dan kedudukan Dewa Wisnu pada masa Hindu-Buddha di Bali abad VII-XIV Masehi. Tujuan penelitian ini adalah untuk merekonstruksi sejarah kebudayaan masyarakat Bali pada masa lalu terutama aspek religinya. Penulis menggunakan metode pengumpulan data seperti studi pustaka, observasi dan wawancara serta pengolahan data melalui analisis ikonografi, ikonoplastik dan komparatif. Teori yang digunakan untuk membantu analisis adalah teori ikonografi dan ikonologi Erwin Panofsky. Berdasarkan hasil penelitian ditemukan bahwa terdapat variasi ikonografi pada arcaarca dewa Wisnu pada masa Hindu-Buddha di Bali abad VII-XIV Masehi. Variasi terlihat pada ragam penggambaran perhiasan, busana, laksana, dan sikap tubuh. Adapun variasi ikonografi disebabkan oleh faktor kemampuan dan kreativitas seniman, batasan sosial, pengaruh budaya dan bahan baku arca. Peranan dan kedudukan dewa Wisnu pada masa Hindu-Buddha di Bali yaitu sebagai dewa pelindung dan pemelihara, kedudukannya sangat penting walaupun tidak setinggi Dewa Siwa.